Variasi Arteri Koronaria Dominan pada Jantung Kadaver di Laboratorium Anatomi Fakultas Kedokteran Universitas Andalas - Gusti Revilla (Faculty of Medicine, Universitas Andalas, 2023)
Coronary arteries have a variable distribution in the myocardium of the heart. This condition is also known as dominant coronary arteries. The research that has been done knows that the most common coronary artery variation is the right dominant variation and the co-dominant variation. Objective: to describe the variation of the dominant coronary arteries in the cadaveric heart at the Anatomy Laboratory of the Faculty of Medicine, Andalas University. Method: This study used a descriptive method of looking at the variation of the dominant coronary arteries in the cadaveric heart at the Anatomy Laboratory of the Faculty of Medicine, Andalas University. The population was all existing cadaveric hearts and the entire population was sampled according to the inclusion and exclusion criteria. Results: The number of samples found was 26 hearts. The results obtained were 80.8% were hearts with a right dominant coronary artery, which was the most varied, 7.7% a heart with a left dominant coronary artery, and 11.5% a heart with a co-dominant coronary artery. Conclusion: Variations of the dominant coronary arteries found ptovides information for the need to increase awareness of these risky variations so that morbidity and mortality can be reduced.